Molecular Docking, ADMET, and Multi-Parameter Optimization (MPO) of Punicalagin-Related Compounds as ADAM17/TACE Modulators Candidate - Mukhammad Asy'ari; Ariztha Delivia Putri; Parsaoran Siahaan (Greensphere: Journal of Environmental Chemistry, 2026)
ADAM17/TACE is an important target in the regulation of inflammatory responses; however, the development of selective modulators remains challenging because conventional approaches generally focus on the catalytic site. Punicalagin-related compounds have been reported to possess potential as metalloprotease modulators, yet the relationship between molecular structure, binding affinity, and pharmacokinetic properties has not been comprehensively investigated. This study aimed to evaluate punicalagin-related compounds including punicalagin (PNG), punicalin (PNL), ellagic acid (ELA), gallic acid (GAA), hexahydroxydiphenic acid (HPA), shikimic acid (SKA), 3-dehydroshikimate (DHS), 3,4-dihydroxybenzoate (DXB), and marimastat (MRM) as a reference inhibitor through an integrated in silico approach involving molecular docking, physicochemical descriptor and drug-likeness analysis, ADMET prediction, and multi-parameter optimization (MPO). This approach also supports green chemistry principles through more efficient early-stage screening of bioactive candidates by reducing the use of reagents and preliminary biological experiments. Docking results showed that PNG and PNL exhibited high binding affinities (−8.2 to −8.8 kcal/mol), but with limitations in membrane penetration, whereas HPA, ELA, and GAA demonstrated moderate affinities with more favorable pharmacokinetic profiles. Physicochemical descriptor and ADMET analyses indicated that smaller metabolites fulfilled drug-likeness criteria and exhibited better bioavailability than larger ellagitannins. MPO evaluation highlighted HPA (0.65) and ELA (0.62) as promising initial candidates with an optimal balance between target interaction and pharmacokinetic feasibility.